Gender imbalance in the maritime industry: impediments, initiatives and recommendations. Issue 1 (2nd January 2017) - MacNeil, Anna; Ghosh, Samrat
ABSTRACT: The reality of a global gender imbalance in the workforce is undeniable. However, it is even more profound in the traditionally male-dominated maritime industry, where women make up a mere 2% of the workforce. Although the maritime industry has adopted initiatives towards closing the existing gender gap, the integration of women into the maritime industry has been at a sluggish rate due to various impediments. This paper not only traces the issue of the gender imbalance to its historical roots but also highlights the current impediments and challenges unique to the maritime industry towards achieving gender equality in its workforce. Using a review of literature, this paper also brings forward the various initiatives put in place to facilitate the integration of women into the maritime sector and suggests recommendations for the same. The paper acknowledges that women are a growing force and the need to close the gender gap is widely accepted. However, even though many initiatives have led to an increase of female presence, there is room for further efforts.